PEMODELAN DIRECT FIELD ORIENTED CONTROL (D FOC PADA PENGATURAN KECEPATAN MOTOR INDUKSI TIGA PHASA - Rizana Fauzi; Jumiyatun Jumiyatun; Maryantho Masarrang (Foristek, 2019)
The 3 phase induction motor in its use is increasingly growing, so research on the speed regulation of the 3 phase induction motor is also increasingly being studied. This is because the use of 3 phase induction motors in industry and especially hybrid vehicles is increasingly being developed. But there are some disadvantages of induction motors, one of which is the characteristics of non-linear parameters, especially rotor resistance which has varying values for different operating conditions, so it cannot maintain its speed constantly if there is a change in load. This of course can affect the performance of an induction motor. To get a constant speed and better system performance on load changes a controller / controller is needed. This study aims to model the parameters used in Direct Field Oriented Control (DFOC) using Matlab SIMULINK. With the controlled dq parameter, the induction motor will be more stable, because the dq parameter determines the stability of the changes in torque and flux in the induction motor. In the results of implementation, it can be seen that the use of DFOC can be used as an approach in the speed regulation of the induction motor. and with the use of PI controls it can help the output response get better with a shorter response time to reach the reference value.